Investment Risk Management for Retail Investors in Indonesia's Digital Capital Market: A Systematic Literature Review - Muhamamd Arif; Muhamamd Syaipudin (General Multidisciplinary Research Journal, 2026)
Introduction: The rapid development of digital technology has transformed investment activities by providing retail investors with easier access to capital market services through digital platforms. While digitalization has increased market participation and investment efficiency, it has also introduced new challenges, including higher market volatility, information overload, behavioral biases, and technology-related risks. These conditions highlight the growing importance of investment risk management as a strategic approach to support rational and sustainable investment decisions among retail investors in Indonesia.Methods: This study employed a qualitative literature review to examine investment risk management in the digital era. The literature search was conducted using the Scopus, Web of Science, and Google Scholar databases. Articles published between 2019 and 2024 were considered to capture recent developments in digital investment and financial technology. The inclusion criteria comprised peer-reviewed journal articles published in English that discussed investment risk management, digital investment platforms, financial literacy, behavioral finance, or technology adoption among retail investors. Conference papers, book chapters, review articles, non-peer-reviewed publications, and studies unrelated to the research objectives were excluded. Following the screening and eligibility assessment, 45 articles were included in the final review. The selected literature was synthesized using a descriptive qualitative approach involving data reduction, comparison of findings across studies, thematic categorization, synthesis of recurring patterns, and interpretation to identify the principal themes and strategies related to investment risk management in the digital era.Results: The findings indicate that digital transformation has significantly changed the investment behavior of retail investors by increasing accessibility, transaction efficiency, and information availability. However, digitalization has also intensified investment risks associated with market uncertainty, behavioral factors, and information quality. The review further reveals that portfolio diversification, financial literacy, and the utilization of digital technologies such as robo-advisors and real-time portfolio monitoring are essential strategies for mitigating investment risks.Conclusion and Suggestion: Investment risk management in the digital era should be implemented through an integrated approach that combines portfolio diversification, financial literacy, and the effective use of digital technology. Retail investors should strengthen their analytical capabilities and critically evaluate digital information before making investment decisions. Future studies are recommended to employ quantitative or mixed-method approaches to examine empirically the relationships among digital financial literacy, behavioral biases, technology adoption, and investment risk management across different groups of investors in Indonesia.